2011
DOI: 10.1055/s-0031-1271114
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of CEUS in the Differential Diagnosis of Small (≤ 20 mm) and Subcentimetric (≤ 10 mm) Focal Liver Lesions in Comparison with Histology

Abstract: CEUS has a high diagnostic accuracy for the differential diagnosis of small and subcentimetric FLLs in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
85
2
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(105 citation statements)
references
References 6 publications
(8 reference statements)
4
85
2
14
Order By: Relevance
“…This technique fails to reliably differentiate between malignant and benign lesions [13,[25][26][27][28][29][30]. Some FLLs are particularly difficult to diagnose even by biopsy because of their small size (<10 mm) or superficial location (close to liver capsule) [12,15,26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This technique fails to reliably differentiate between malignant and benign lesions [13,[25][26][27][28][29][30]. Some FLLs are particularly difficult to diagnose even by biopsy because of their small size (<10 mm) or superficial location (close to liver capsule) [12,15,26].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that transabdominal CEUS with low frequency convex transducer is significantly better than unenhanced BMUS for the detection [1,3] and classification [7,10,33] of FLLs. For unclear small FLLs which could not be characterized with confidence by using transabdominal BMUS or Doppler ultrasound techniques, real-time CEUS has demonstrated the ability to characterize them reliably [1,12,21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CEUS has been widely used in many different applications, especially in the detection and diagnosis of FLLs [28] . In many clinical trials, CEUS has shown high performance comparable to CECT and CEMRI in detection and characterization of FLLs [29][30][31] . Malignant FLLs, especially liver metastasis usually present arterial rim-like or homogeneous hyper-enhancement with "defect of enhancement" during the late phase or liver specific phase of CEUS, which makes the characterization and detection as accurate and easy as CECT [32] .…”
Section: Introductionmentioning
confidence: 99%